Causal effects of gut microbiota on the risk of periodontitis: a two-sample Mendelian randomization study - Luo, Shulu; Li, Weiran; Li, Qianqian; Zhang, Mengqi; Wang, Xun; Wu, Shuyi; Li, Yan (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The oral cavity and the gut tract are interconnected, and both contain abundant natural microbiota. Gut microbiota may interact with oral flora and participate in the development of periodontitis. However, the specific role of certain gut microbiota taxa for periodontitis has not been investigated. Mendelian Randomization is an ideal method to explore causal relationships avoiding reverse causality and potential confounding factors. Thus, we conducted a two-sample Mendelian Randomization study to comprehensively reveal the potential genetic causal effect of gut microbiota on periodontitis. Methods SNPs strongly associated with 196 gut microbiota taxa (18,340 individuals) were selected as instrument variables, and periodontitis (17,353 periodontitis cases and 28,210 controls) was used as the outcome. The causal effect was analyzed via random effect inverse variance-weighted, weighted median, and MR-Egger. The sensitivity analyses were conducted using Cochran’s Q tests, funnel plots, leave-one-out analyses, and MR-Egger intercept tests. Results Nine gut microbiota taxa (Prevotella 7, Lachnospiraceae UCG-008, Enterobacteriales, Pasteurellales, Enterobacteriaceae, Pasteurellaceae, Bacteroidales S24.7 group, Alistipes, and Eisenbergiella) are predicted to play a causal role in enhancing the risk of periodontitis (p < 0.05). Besides, two gut microbiota taxa (Butyricicoccus and Ruminiclostridium 6) have potentially inhibitive causal effects on the risk of periodontitis (p < 0.05). No significant estimation of heterogeneity or pleiotropy is detected. Conclusions Our study demonstrates the genetic causal effect of 196 gut microbiota taxa on periodontitis and provides guidance for the clinical intervention of periodontitis.